Experiential learning exercise: Designing a pirate community using the cultural web (Journal of Applied Learning and Teaching, 2022)
The purpose of this experiential learning design article is threefold: firstly, to provide an opportunity for icebreaking or community building using a team-based activity, secondly, to apply Johnson and Scholes’ cultural web framework in a performative, open space learning context of the historic pirate culture, and finally, to connect the learning experience to job hunting, specifically helping students assess their fit with potential employers.This group exercise requires participants to use and integrate a variety of concepts from marketing and strategy, and then subsequently reflect on their performance with an after-action review. The exercise is likely to be most appropriate for advanced undergraduate and master’s classes, however, it has also been used successfully for community engagement on a foundation year. It would appear to be particularly useful for professional development, management, leadership, and organisational modules where a lean-in, experiential-oriented pedagogy is deployed.